2002
DOI: 10.1063/1.1505670
|View full text |Cite
|
Sign up to set email alerts
|

First- and second-order Raman spectra of galena (PbS)

Abstract: Raman spectra of cleaved, millimeter-sized single crystals of mineral galena (PbS) have been measured between 100 and 1200 cm−1 over the temperature range 80 to 373 K. Three low wave number bands are observed which can be reconciled with the results of earlier reports. However, changes in the peak wave numbers and in the relative intensities of these bands in response to changes in temperature do not conform with previous assignments for the observed bands. Detailed assignments are proposed which are based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
77
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 27 publications
11
77
1
3
Order By: Relevance
“…the usual behavior for the shifts of phonons with temperature) and a few other weak bands already reported in Refs. [8,11,12]. Fig.…”
Section: Comparison With the Experiments And Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the usual behavior for the shifts of phonons with temperature) and a few other weak bands already reported in Refs. [8,11,12]. Fig.…”
Section: Comparison With the Experiments And Discussionmentioning
confidence: 99%
“…Going farther into the visible (in the green, for example, at 514 nm, see + -ion laser) results in very weak intrinsic second-order spectra. Laser excitation around 647 nm seemed to be a good compromise between low background and reasonable signal-to-noise level (possibly aided by a weak resonance effect in the red [11]). Another important experimental detail is the power level of the laser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the inset, it is observed that the spectrum shows emission peaks at 173 cm −1 , 265 cm −1 and 481 cm −1 . The band centered at 173 cm −1 might have originated from the combination of longitudinal and transverse acoustic phonon modes associated with PbS crystal [19]. The peak at 265 cm −1 may be related to PbO formation due to photodegradation of PbS [20].…”
Section: Raman Studiesmentioning
confidence: 99%
“…However, at the NaCl phases of all PbX, the forbidden first-order spectra preceding surface oxidation were still established under the variation of the laser line or the increase in laser power. [9][10][11][12][13][14][15][16][17][18][19] In the present work, we investigated the above phase transition in Pb 1-x Sn x Se (x=0.125) by Raman spectroscopy under a pressure of up to 6 GPa. Sn dopant was reported to decrease the transition pressure from 4.5 to 3 GPa.…”
Section: Introductionmentioning
confidence: 99%